2022
DOI: 10.1038/s42003-022-04125-x
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome-level genome and population genomics reveal evolutionary characteristics and conservation status of Chinese indigenous geese

Abstract: Geese are herbivorous birds that play an essential role in the agricultural economy. We construct the chromosome-level genome of a Chinese indigenous goose (the Xingguo gray goose, XGG; Anser cygnoides) and analyze the adaptation of fat storage capacity in the goose liver during the evolution of Anatidae. Genomic resequencing of 994 geese is used to investigate the genetic relationships of geese, which supports the dual origin of geese (Anser cygnoides and Anser anser). Chinese indigenous geese show higher gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 91 publications
1
3
0
Order By: Relevance
“…Chinese domestic geese other than Yili geese are genetically closely related to swan geese, while Yili geese and two European domestic geese (Landaise geese and Roman geese) are genetically close to greylag geese; these findings suggest that Chinese domestic geese (except Yili) may originate from swan geese while Yili geese, Landaise geese, and Roman geese may originate from greylag geese. This is supported by previous population analyses [ 9 , 10 , 11 ]. In the European group, we note that the Rhine goose had almost half admixed background with Chinese domestic geese, and it constituted a separate population but was genetically closely related to Chinese domestic breeds.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Chinese domestic geese other than Yili geese are genetically closely related to swan geese, while Yili geese and two European domestic geese (Landaise geese and Roman geese) are genetically close to greylag geese; these findings suggest that Chinese domestic geese (except Yili) may originate from swan geese while Yili geese, Landaise geese, and Roman geese may originate from greylag geese. This is supported by previous population analyses [ 9 , 10 , 11 ]. In the European group, we note that the Rhine goose had almost half admixed background with Chinese domestic geese, and it constituted a separate population but was genetically closely related to Chinese domestic breeds.…”
Section: Discussionsupporting
confidence: 90%
“…It is one of the first domesticated poultry: Chinese domestic goose was domesticated over 7000 years ago [ 7 ], and European domestic goose was domesticated approximately 5000 years ago [ 8 ]. It seems to be an indisputable fact that there are two origins for domestic geese [ 9 , 10 , 11 ]: Chinese domestic geese (except Yili geese) originate from the swan goose ( Anser cygnoides ), and European domestic geese and Yili geese originate from the greylag goose ( Anser anser ). However, these results are not conclusive because there are still many goose breeds not included in these studies.…”
Section: Introductionmentioning
confidence: 99%
“…The remaining high‐quality paired‐end reads were mapped to the Xingguo Grey reference genome (Ouyang et al, 2022) using the burrows–wheeler aligner (version 0.7.8) with the command line ‘BWA mem ‐t 8 ‐k 32 ‐M’. To reduce mismatches generated by PCR amplification before sequencing, duplicated reads were removed with the help of samtools (Li et al, 2009; Li & Durbin, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…Questions about where and when the domestication occurred, the associated genetic changes and the subsequent history of domestic geese remain largely unresolved. Recent studies have revealed complex genetic relationships between wild and domesticated populations and the development of advanced genetic sequencing technologies have allowed researchers to study the genomes of geese in unprecedented detail, unlocking new insights into the evolutionary history of these birds (Heikkinen et al, 2015; Ouyang et al, 2022; Ren et al, 2016). Through comparative genomic analysis, previous studies have identified several domestication selection genes, such as PRKAB1 and PRKAG2 , which are related to growth and development, feed intake and meat feed efficiency, as well as pathways involved in growth reproductive metabolism regulation (Liu et al, 2021; Zhou et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Xi et al discovered a significant correlation between the presence of a 14 bp insertion mutation in exon 3 of the EDNRB2 gene and the white feather phenotype observed in Sichuan Gang geese [5]. Yang et al and Ouyang et al also reported an association between the same 14 bp insertion mutation in the EDNRB2 gene and the white feather phenotype found in swan geese [9,10]. Ren et al screened 26 genes related to goose feather color formation, including KITLG, MITF, TYRO3, and KIT [11].…”
Section: Introductionmentioning
confidence: 97%